PENYEBARAN PAHAM POOP CULTURE MELALUI WORLD TOILET ORGANIZATION DI SWISS - Arini, Anisyah Puput; Rani, Faisyal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research describes the Spreading Thought of Poop Culture by World Toilet Organization (WTO) in Switzerland. The international world faces many problems, with one of them being environmental issues. These environmental issues arise from social movements of people who recognize the importance of the environment, especially regarding the issue of the toilet. Japan is the first country to discuss the issue of toilet problems as well as making poop culture become part of its pop culture. Japan has also created its own national organization named Japan Toilet Association (JTA) where it aims to spread the awareness of poop culture within the country as well as branch out abroad to other countries worldwide. This research consists of how WTO assists Japan in the deployment of poop culture as well as illustrates how poop culture has developed in the participating countries of WTO, with main focuses applied to Switzerland where influences from WTO were evident in governmental decision-making with regards to the toilet and sanitary affairs of the country.Keywords: Toilet, Poop culture, World Toilet Organization, Swiss Toilet Association, Japan Toilet Association